Rumus Mengajar Matematika Dengan Humor untuk Pembelajaran Joyful Guru SD dan SMP - Novrita Widiyastuti; Rizka Septiana (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
Community service program “Teaching Math with Humor” came from government appeal to strengthen this subject since elementary school and has objective to answer the problem of the high anxiety of students regarding mathematics subject, also to increase teachers’ knowledge of humor in the class. IHIK3 as partner has many references about humor in the education, but has obstacle in translations, also has not yet have material that special designed for elementary and secondary school. On the other side, BPMP Province of DKI Jakarta had identified teachers’ needs of teaching method that more joyful, humanist and relevant with deep learning principal. Based on these things, LSPR Institute of Communication and Business collaborates with IHIK3 and BPMP DKI Jakarta design program with name “Formula of Teaching Math x Humor”. The program implementation method consists of 3 stages: 1) Preparation: compiling the materials of the training and evaluation instruments of pre-test and post-test; 2) Implementation: hybrid training for math teachers with 2 primary sessions, “Formula of Teaching with Humor” and “Formula of Witty Math”; 3) Evaluation: activity result report. The evaluations were conducted through quantitative descriptive analysis to pre-test and post-test results. The results of the activity show significantly increasing in knowledge, skills and teachers’ ethics aspect on using humor when teaching math. The comprehension of the participants regarding insert humor techniques was increasing from 13,1% to 73,2%, while the ability to mention about humor formula and demonstrating educative humor examples also has a substantial increase. Most of the participants (94,6%) stated that the training had fulfilled their expectation and gave new insights to create learning that is more joyful. This program shows that humor can be a pedagogic strategy to difficult subject such as mathematics. Similar program should be conducted more and deeper, because it is give benefits to students as well as their teachers.